Advanced integrated power generation centre for future More-Electric Aircraft - Lang, Xiaoyu (2021)
The More-Electric Aircraft (MEA) concept is a major trend in aircraft electrical power system engineering and results in an increase in onboard electrical loads and electrical power demand. On an aircraft the jet engine acts as the prime power source, providing to the onboard systems pneumatic power, hydraulic power, mechanical power and electrical power. As the aerospace industry is moving towards the MEA paradigm, many functions which are conventionally driven by pneumatic, hydraulic and mechanical power systems are being replaced by their electrical counterparts. However, due to the power off-take limit from the high-pressure (HP) spool, extra power is considered to be extracted from the low-pressure (LP) spool of an engine through the coupled generators. Increased number of generators and power electronic penetration renders a higher requirement to the power generation centre (PGC) in a more electric engine in terms of controllability, stability, fault tolerance, and power flow flexibility.